(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Agile IT project management has been a paradigm shift in the information technology industry.Traditional project management techniques often failed to keep up in an era marked by quick technicalbreakthroughs and constantly changing client needs. But agile provides a flexible and dynamic frameworkthat is well suited to the dynamic nature of IT projects. This strategy places a high value on teamwork,adaptability, and customer focus while encouraging a culture of responsiveness and continualdevelopment. This review will dive into the core principles, processes, and essential ideas that make upAgile IT project management. We’ll examine how this approach has transformed the way IT projects arecarried out and why it has become crucial for businesses looking to flourish in the digital era. An outlineof agile tech project management is provided in this document.